Phytochemical Analysis and Evaluation of Anticonv149-158 ulsant Effect of Chamomile (Matricaria chamomilla L.) Flower Extract in Chicks - Seedo, Salam Kamal; Ali, Jian Salam Hassan (Sulaimani Journal for Pure and Applied Sciences, 2017)
This study was carried out to investigate the effect of chamomile flower aqueous extract on different biochemical parameters in pentylenetetrazole (PTZ) induced-convulsive chicks. Parameters included were serum total antioxidant capacity (T-AOC), serum and brain gamma-aminobutyric acid (GABA), serum cholinesterase enzyme activity (ChE), electrolytes (Na+,K+, and Cl-), total calcium (Ca2+), serum glucose and total protein concentration. The dried flowers parts of chamomile (Matricaria chamomilla L.) were subjected to aqueous extraction and given at (200, 400 and 600mg/kg orally), for its anticonvulsant effects and the effect was compared with the standard anticonvulsant drug sodium valproate (200mg/kg). A dose of 200mg/kg showed full protection against PTZ convulsions, whereas doses of 400 and 600 mg/kg reduced the latency and onset of convulsion. The results suggest that the aqueous extract of chamomile flower may produce anticonvulsant effects via biochemical changes including significant increases in serum T-AOC, serum GABA, serum ChE activity and Na+, and a significant reduction in K+ and serum glucose concentration have been observed.
Keywords: Matricaria chamomilla L; PTZ; TAOC; GABA